2010
DOI: 10.1016/j.bcp.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional up-regulation of SOD1 by CEBPD: A potential target for cisplatin resistant human urothelial carcinoma cells

Abstract: Bladder cancer is the fourth most common type of cancer in men (ninth in women) in the United States. Cisplatin is an effective agent against the most common subtype, urothelial carcinoma. However, the development of chemotherapy resistance is a severe clinical problem for the successful treatment of this and other cancers. A better understanding of the cellular and molecular events in response to cisplatin treatment and the development of resistance are critical to improve the therapeutic options for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 61 publications
2
56
0
1
Order By: Relevance
“…This study, together with two recent reports (25,31), underscores a multifaceted impact of C/EBPδ on the DNA damage response. By promoting cyclin D1 degradation (25), C/EBPδ may augment growth arrest to allow DNA repair to proceed.…”
Section: Discussionsupporting
confidence: 68%
“…This study, together with two recent reports (25,31), underscores a multifaceted impact of C/EBPδ on the DNA damage response. By promoting cyclin D1 degradation (25), C/EBPδ may augment growth arrest to allow DNA repair to proceed.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, STAT3 pathway inhibition has been shown to result in growth arrest, apoptosis, and chemosensitivity in several human malignancy models (50). We previously demonstrated that CEBPD inhibition increased UCUB sensitivity to CDDP (19). In this study, we demonstrated that CEBPD attenuation in UCUB and CDDPresistant UCUB cells sensitized them to CDDP and CDDPinduced paclitaxel resistance (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to acting as a tumor suppressor, several recent reports have suggested that CEBPD plays an oncogenic role under certain conditions (17,18). Furthermore, CEBPD attenuation can sensitize CDDPinduced cell death in CDDP-resistant UCUB cells (19). However, the details remain largely unclear, and the improvement in CEBPD activation following CDDP and paclitaxel cross-resistance remains uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…CEBPD participates in the induction of genomic instability inducers, including aurora kinase C, superoxide dismutase 1 (SOD1), and COX-2 (28,44). Genomic instability has been suggestively linked to anticancer drug resistance and cancer reoccurrence (44).…”
Section: Discussionmentioning
confidence: 99%